The Essence and Content of State Regulation of Services Development in Conditions of Increasing Autonomy of Federal State Entities - Ivanov, Vasily G.; Barabanova, Svetlana V.; Shagieva, Rozalina V.; Chikisheva, Natalia M.; Lunev, Alexander N.; Volkova, Natalya V.; Nabiullina, Karina R.; Spirina, Elena V. (International Review of Management and Marketing, 2016)
The relevance of the study is reasoned by the development of services, as a component of balanced socio-economic development of territories in a Federal state. The purpose of the article is to determine the essence and content of state regulation of services' development in conditions of increasing autonomy of federal state's entities. A leading approach is the institutional one that considers state regulation of service sector's development in the Federal state as a purposeful system of measures of state control that contributes to maximizing of the assets' value of the service sector in the process of socio-economic activities and is aimed at ensuring of a balanced socio-economic development of regions. The service sector is one of the most dynamic and growing segments of regional markets, as well as one of the characteristics of effective socio-economic policy in the region. The yield growth from the service sector's assets while risk diversification will ensure the development of regional services markets, meeting the needs of the population for public goods and improving of the quality of life. The article identifies and scientifically justifies objects, actors, principles, methods and tools of state regulation of services' development in a Federal state. The paper submissions can be useful for specialists of Federal and regional authorities, local governments, line ministries, scientists interested in issues of regional economy and services' management. Keywords: Socio-Economic Development, Inter-Territorial Differentiation, Content of State Regulation, Management of Service Sphere. JEL Classifications: H53, H83, O35